Reviewing The Handling Of Covid-19 In Indonesia In The Perspective Of The Pancasila Element Theory (TEP) - I Gusti Ngurah Santika; I Made Kartika; I Gusti Ayu Mas Darwati (Universitas of Muhammadiyah Makassar, 2021)
The purpose of this research was to review the handling of Covid-19 in Indonesia using the Pancasila Element Theory (TEP). The method used in this research was descriptive qualitative. Data collection methods used in this research were documentation and literature studies. Based on the Pancasila Element Theory, the handling of Covid-19 in Indonesia can be viewed from the problems, thoughts, ideas, acceptance, agreement, truth, and peace. The results of this research indicated that Covid-19 with its characteristics was a problem that encourages the emergence of thoughts from competent people. From that thought, various ideas were born in the form of appeals and regulations issued by the Government. However, citizen acceptance of the Government's efforts to prevent the spread of Covid-19 in Indonesia was very low. This happened because of a disagreement between the Government and its citizens in viewing Covid-19. If so, it is impossible for the handling of Covid-19 in Indonesia to be done properly. This means that the handling of Covid-19 in Indonesia contains problems, so it is impossible to achieve peace. Tujuan penelitian ini untuk meninjau penanganan Covid-19 di Indonesia dengan menggunakan Teori Elemen Pancasila (TEP). Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Metode pengumpulan data yang digunakan dalam penelitian ini adalah studi dokumentasi dan literature. Berdasarkan Teori Elemen Pancasila penanganan Covid-19 di Indonesia dapat ditinjau dari permasalahan, pemikiran, gagasan, penerimaan, kesepakatan, kebenaran, dan kedamaian. Hasil penelitian ini menunjukan, bahwa Covid-19 dengan karakteristiknya merupakan permasalahan yang mendorong munculnya pemikiran dari orang-orang kompeten. Dari pemikiran itu, lahirlah berbagai gagasan dalam bentuk himbauan dan aturan yang dikeluarkan Pemerintah. Tetapi rendah sekali penerimaan warga terhadap usaha Pemerintah dalam mencegah penyebaran Covid-19 di Indonesia. Hal itu terjadi karena adanya ketidaksepakatan antara Pemerintah dengan warganya dalam memandang Covid-19. Kalau begitu tidak mungkin penanganan Covid-19 di Indonesia bisa dilakukan dengan benar. Berarti penanganan Covid-19 di Indonesia mengandung permasalahan, sehingga tidak mungkin tercapai kedamaian.